Sacha inchi (Plukenetia volubilis L.) Oil Ameliorates Hypertensive and Vascular Remodeling in Nitric Oxide Synthase Inhibitor-Induced Hypertensive Rats - Sa-nguanpong, Pakaporn; Thongsit, Anatcha; Boonsang, Jhantanipa; Inchan, Anjaree; Kaewkong, Worasak; Hanchang, Wanthanee; Chootip, Krongkarn; Bualeong, Tippaporn (Journal of Basic and Applied Pharmacology, 2023)
Sacha inchi (SI) oil possesses a wealth of vital polyunsaturated fatty acids (PUFA), vitamin E (including γ- and δ-tocopherols), and beneficial antioxidants like phenolic compounds, making it highly recommended for promoting heart health. Therefore, our ambition was to analyze the potential anti-hypertensive effect of SI oil on cardiovascular remodeling in nitric oxide synthase inhibitor-induced hypertensive rats. Hypertension was provoked in male Sprague-Dawley rats by daily handling of L-NAME through their drinking water at a dose of 40 mg/kg for three weeks. The rats were then administrated with L-NAME in drinking water plus SI oil 0.5, 1.0, 2.0 ml/kg/day or captopril 5 mg/kg/day which was delivered via oral gavage for 5 weeks. All rats had their tail cuff blood pressure measured weekly. Upon completion of the experiment, the measurement of direct blood pressure was conducted by cannulating the common carotid artery. Plasma nitric oxide metabolites (NOx), levels of the adhesion molecule VCAM-I, cardiac histopathology, fibrosis in cardiac muscle, and aorta were also investigated. SI oil at 2.0 ml/kg administered once daily for 5 weeks significantly reduced SBP, DBP, MAP, and decreased VCAM-I and fibrosis in hypertensive rats. Furthermore, SI oil also mitigated endothelial dysfunction by enhancing the vascular response to acetylcholine (ACh) in aortic rings. Taken together, these results indicated that SI oil attenuated blood pressure and improved vascular dysfunction. However, the protective effect of SI oil will be further studied because the damage to organs from hypertension is difficult to restore after pathological damage has occurred.